Expedient Synthesis of Ketones via N‐Heterocyclic Carbene/Nickel‐Catalyzed Redox‐Economical Coupling of Alcohols and Alkynes - Li, Yu‐Qing; Li, Feng; Shi, Shi‐Liang (Chinese journal of chemistry, 2020)
An N‐heterocyclic carbene/Ni‐catalyzed direct coupling of alcohols and internal alkynes for a convenient synthesis of α‐branched ketones is reported. This novel transfer hydrogenation protocol provides an atom‐, and redox‐economical approach to α‐branched ketones, products that are difficult to access through the hydroacylation of unactivated internal alkenes with aldehydes, in one chemical step. Summary of main observation and conclusion An N‐heterocyclic carbene/nickel‐catalyzed direct coupling of alcohols and internal alkynes to form α‐branched ketones has been developed. This methodology provides a new approach to afford branched ketones, which are difficult to access through the hydroacylation of simple internal alkenes with aldehydes. This redox‐neutral and redox‐economical coupling is free from any oxidative or reductive additives as well as stoichiometric byproducts. These reactions convert both benzylic and aliphatic alcohols and alkynes, two basic feedstock chemicals, into various α‐branched ketones in a single chemical step.